Educational Management Practices for Enhancing Triple Helix Partnerships in Building Inclusive Society Through Technical and Vocational Education and Training in Rivers State Universities (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study examines educational management practices for enhancing triple helix partnerships in building inclusive society through technical and vocational education training in Rivers State. Three questions were answered with corresponding null hypotheses that were formulated and tested at 0.05 level of hypotheses guided the study. The study employed the descriptive research survey design and was carried out in Rivers State Universities. The population of the study was 180 respondents (Government = 18, Industries = 143, Universities = 19). Due to small population size of the respondents, there was no sampling as the entire population was used and hence, it was a census study. The instrument for data collection was a self-structure questionnaire tagged “Educational Management Practices for Enhancing Triple Helix Partnerships Questionnaire (EMPETHPQ)” which was design and patterned after a modified Likert – 4-point rating scale of agreement. The instrument was validated and tested for reliability through test-retest method. A reliability coefficient of 0.83 was established using Pearson Product Moment Correlation (PPMC) coefficient. Data collected were analysed using mean descriptive statistics to answer the research questions while one way ANOVA was used to test the hypotheses. The study found that educational management practices that enhance triple helix partnership in TVET are resource allocation, curriculum management and monitoring, evaluation and quality assurance practices. Based on the findings of the study, it was recommended among others that there should be equitable distribution of financial resources among university, industry, and government partners in TVET programmes. There should be collaboration between the university, industry and government when developing and reviewing TVET curriculum to ensure that it captures the three tiers needs. The UIG should regularly supervise, monitored and evaluate TVET programmes based on collaboration with university - industry - government.